2020
DOI: 10.3390/app10217785
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Calibration of the FT-IR Spectroscopy on Concentration of Heavy Metal Ions in River and Borehole Water Sources

Abstract: Heavy metals in water sources can threaten human life and the environment. The analysis time, need for chemical reagents, and sample amount per analysis assist in monitoring contaminants. Application of the Fourier Transform Infrared (FT-IR) Spectroscopy for the investigation of heavy metal elements has significantly developed due to its cost effectiveness and accuracy. Use of chemometric models such as Partial Least Square (PLS) and Principle Component Regression Analysis (PCA) relate the multiple spectral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Earlier studies showed that the FTIR spectroscopy provided satisfactory results with high-throughput screening framework of numerous biomolecules in several food samples mainly fruits, vegetables, or beverages, e.g., biosynthesis of silver nanoparticles in figs ( Jacob et al, 2017 ), Sudanese honey ( Tahir et al, 2017 ), discrimination of bovine, porcine and fish gelatins ( Cebi et al, 2016 ), fatty acid changes in Caenorhabditis elegans ( Bouyanfif et al, 2019 ), mini kiwi ( Baranowska-Wójcik and Szwajgier, 2019 ), red bell pepper ( Prabakaran et al, 2017 ). Therefore, FTIR spectroscopy has emerged as a potential alternative for highly rapid metabolic fingerprinting technique, which can be applied in conjunction with an attenuated total reflection (ATR) correction procedure ( Mamera et al, 2020 ). However, FTIR provides complex spectra, which consists of many related variables (wavenumber) per sample, making its visual analysis very difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies showed that the FTIR spectroscopy provided satisfactory results with high-throughput screening framework of numerous biomolecules in several food samples mainly fruits, vegetables, or beverages, e.g., biosynthesis of silver nanoparticles in figs ( Jacob et al, 2017 ), Sudanese honey ( Tahir et al, 2017 ), discrimination of bovine, porcine and fish gelatins ( Cebi et al, 2016 ), fatty acid changes in Caenorhabditis elegans ( Bouyanfif et al, 2019 ), mini kiwi ( Baranowska-Wójcik and Szwajgier, 2019 ), red bell pepper ( Prabakaran et al, 2017 ). Therefore, FTIR spectroscopy has emerged as a potential alternative for highly rapid metabolic fingerprinting technique, which can be applied in conjunction with an attenuated total reflection (ATR) correction procedure ( Mamera et al, 2020 ). However, FTIR provides complex spectra, which consists of many related variables (wavenumber) per sample, making its visual analysis very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the chemometric and data mining approaches are usually applied to simplify or dimensionally reduce the dataset to fewer independent parameters, with a minimal loss of total variance, thereby making human interpretation easier ( Lu et al, 2011 ). Achieving reproducible results, spectra dimensionality reduction and high fingerprinting throughput acquisition requires a rigorous use of chemometric models capable of associating the numerous spectral intensities from multiple calibration samples to identify chemical fingerprints within samples by removing potential outliers and determining the principal components capturing the high amount of total variance within the dataset ( Mamera et al, 2020 ). The most commonly used multivariate calibrations is partial least squares (PLS), which is an appropriate method for predistortion when highly collinearity is present within the dataset.…”
Section: Introductionmentioning
confidence: 99%
“…This would be due to the functional groups of the clay and hydrocolloid that would be responsible for the complexation of Pb 2+ and Cd 2+ and Zn 2+ , due to the O and N binding atoms [ 15 , 79 , 80 ]. Likewise, this would be due to the synergistic effect of the functional groups -OH of Al-OH and Si-OH of the octahedral sheet in the activated clay and -NH and -OH of the hydrocolloid [ 40 , 41 , 80 , 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals concentration in pit latrines is lower than reported in wastewater sludge [52]. However, heavy metal elements are one of the main persistent contaminants of pit latrine leaching or municipal wastewater [48,53]. The persistence of heavy metals in effluent is caused by their non-biodegradable and harmful nature [54].…”
Section: Heavy Metal Composition Of Faecal Sludgementioning
confidence: 99%
“…Metals are mobilized and transported into the food web because of the leaching process from waste dumps, polluted soils, and water [55]. The most common toxic heavy metals in wastewater and sewage sludge include arsenic (As), lead (Pb), mercury (Hg), cadmium (Ca), chromium (Cr), copper (Cu), nickel (Ni), silver (Ag), and zinc (Zn) [48,53,[56][57][58][59]. There is increasing evidence linking Hg, Pb, As, and Cd toxicants to the incidence of cognitive impairments and cancers in children [60].…”
Section: Heavy Metal Composition Of Faecal Sludgementioning
confidence: 99%